FREQUENCY OF SUBCLINICAL HYPOTHYROIDISM AMONG DIAGNOSED CASES OF CHOLELITHIASIS - Riffat Arbab; Khan, Muhammad iqbal; Abdullah Khan; Maria Mehmood; Aisha Arshad; Hafsa Qazi (Journal of University Medical & Dental College, 2020)
Abstract BACKGROUND & OBJECTIVE: Thyroid hormones act as foundation for the normal functioning of all the body hormones and body metabolism. The abnormality of thyroid hormones may lead to deranged lipid metabolism with abnormal relaxation of sphincter of oddi. This will cause stasis of bile in gallbladder and biliary channels leading to stone formation. The objective of the study is to determine the frequency of subclinical hypothyroidism among diagnosed cases of Cholelithiasis. METHODOLOGY: This study was conducted in Surgical Department, Sandman Provincial Hospital Quetta, from January to December 2018. The study has been approved by the ethical review committee of Post Graduate Medical Institute Quetta. It is a cross-sectional study. A total of 193 patients with Cholelithiasis were included in the study. After informed written consent, blood was sent to laboratory for testing the levels of serum TSH, T3 and T4. Samples having TSH values more than 6.0mU/L and serum thyroxin within the normal range 9.0-19.0pmole/L, were labeled as subclinical hypothyroidism. RESULTS: The data of all the patients between 35 to 62 years of age with Cholelithiasis during the study period was taken and analysis was performed. The inclusion and exclusion criteria were strictly considered. Mean ± SD of age was 47.03±5.401 with C.I (46.26-47.80) years. Out of 193 patients 25 (13%) were male and 168(87%) were female. Subclinical hypothyroidism was found to be in 16 (8.16%) patients and remaining 177(91.70%) patients were found normal. CONCLUSION: It was concluded that the incidence of subclinical hypothyroidism in Cholelithiasis patients is low.